Analysis of Digital Marketing Implementation on ASN Customer Acquisition at Bjb KCP Ciledug - Aini Sahaya; Evania Nadzar; Gama pratama (Ecobankers : Journal of Economy and Banking, 2026)
This research aims to evaluate the implementation of Bank BJB's digital marketing in attracting State Civil Apparatus (ASN) customers at BJB KCP Ciledug. Even though Bank BJB has made digital changes by developing services such as BJB Digi and DigiCash, interviews conducted show that the implementation of digital marketing in branches is still very limited. Promotion for ASN credit is only carried out via WhatsApp messages without any organized digital strategy on social media or other digital platforms. On the other hand, recruiting ASN customers still relies more on a relationship marketing approach by establishing closeness between Account Officers (AO) and government agencies. These findings indicate that there is a digital gap between the strength of BJB's digital capacity and digital marketing practices that have not been optimal. By applying a descriptive qualitative approach, this research shows that acquisition methods are still conventional and rely heavily on trust, commitment and personal interaction. This research concludes that there is a need to optimize digital marketing strategies to strengthen the ASN acquisition process, increase marketing effectiveness, and support AO performance amidst increasingly fierce digital banking competition.